The Use of Digital Literacy as a Learning Innovation in Islamic Education Subjects - Marganingrum, Shinta; Shahib, Muhammad Wildan (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2023)
Learning in the 4.0 era has integrated technology into it; technology has become the main component in the implementation of learning. This study aims to explore and analyze the use of digital literacy as an innovation in Islamic Education. The research method used was qualitative with a field study approach, involving Islamic Religious Education teachers and the Technology Science Team at Muhammadiyah Al-Kautsar High School. Data collection techniques used in this study is interviews and documentation to strengthen arguments and the accuracy of data from observations. Besides that, researchers also conduct content analysis on the official website of Muhammadiyah Al-Kautsar High School. The findings of this study show that the application of digital literacy in learning can be a learning innovation, particularly in the focus of this study, namely on Islamic Education Subjects. This research focuses on understanding how digital literacy can be applied in the context of Islamic Education learning, as well as its impact on student participation and student understanding of Islamic teachings.